Interaction of cAMP with the cell-surface receptor induces cell-type-specific mRNA accumulation in Dictyostelium discoideum. - Oyama, M (1986)
The accumulation of many postaggregative mRNA species in Dictyostelium discoideum is dependent upon the continuous presence of elevated levels of cAMP. We have analyzed the cyclic nucleotide specificity of this requirement and show that it is similar to that of the cell-surface receptor and distinct from the specificity displayed by the cAMP-dependent protein kinase. The same specificity is displayed for the accumulation of two classes of prespore mRNAs (class I, early; class II, late) and a prestalk mRNA and for the shutoff of a growth-phase mRNA. Under conditions in which cAMP phosphodiesterase activity is competitively inhibited, half-maximal accumulation of prestalk mRNA can be obtained at cAMP concentrations of 320-520 nM, whereas a higher concentration, 1-2 microM, is required for half-maximal accumulation of the prespore mRNAs and shutoff of the growth-phase mRNA. These effects of cAMP and its analogues on gene expression have been obtained under conditions in which cAMP-mediated activation of adenylate cyclase is completely inhibited. We conclude that cAMP acts to stimulate postaggregative gene expression by interacting at the cell-surface receptor.